Interpretation of Navruz in Navoi’s work.: International Journal of Progressive Sciences and Technologies - Rajabova, Marifat (FILOLOGIYA UFQLARI JURNALI, 2023)
Maqolada adabiyot shinoslikmasalari tahlil va taqdit qilingan